The Pengembangan Media Powerpoint Interaktif Berbasis Karakter Materi Tema 8 Lingkungan Sahabat Kita Pada Subtema 2 Kelas V Sekolah Dasar Negeri Borowetan - Ade Dwi Cahyani (Dharmas Education Journal (DE_Journal), 2022)
This research and development research to develop and determine the feasibility of interactive powerpoint media based on the material in theme 8 of our friend's environment in sub-theme 2 as a learning medium for fifth grade elementary school students. Learning media is a tool that can be used to assist the process of teaching and learning activities that aim to provide a stimulus response to students so that learning becomes easy.. This study uses a development model R n D from Sugiyono, namely ADDIE (Analysis, Design, Development, Implementation, and Evaluation.). The feasibility of character-based interactive powerpoint media was obtained from the validation results of media experts, material experts, and assessments by practitioners. The average value of the media expert's validation results, which is 3.61, is included in the "very valid" category or very feasible to use. The results of the validation by material experts, namely 3.16, are included in the "valid" category or suitable for use. Meanwhile, the average result of the assessment by practitioners is 3.72 which is included in the "very valid" category or very feasible to use. The practicality of character-based interactive powerpoint media was determined from the results of student response questionnaires. The average value of the student's response to the small-scale trial was 3.59, the medium scale was 3.53 and the operational scale was 3.57. Thus, the results of the assessment of student responses to the media are said to be very practical.